(untitled) (International relations and international law Journal, 2016)
Interregional convergence experience of the European Union and Central Asia deserves attention and critical approaches, particularly in the development of strategic partnership. Prospects for partnership between the EU – RC discussed by analyzing key trends, especially in the trade and economic sphere.